The Impact of Artificial Intelligence on Accounting - Mirzaie , Fahimeh (AI and Tech in Behavioral and Social Sciences, 2025)
Artificial intelligence (AI) is a powerful tool that can make accounting processes faster, more accurate, and more efficient. AI can perform repetitive and tedious tasks, reduce human error, enable continuous auditing, and enhance the security and accuracy of audits. However, AI also presents challenges. The cost of acquiring and training AI-based systems can be high. Additionally, AI may lead to a reduction in accounting jobs. AI requires human oversight and control to prevent misuse and fraud. AI may also encounter ethical, legal, and tax-related issues. Furthermore, AI in accounting requires continuous development and updating to align with new needs and environmental changes. AI, due to its capacity to improve and transform the way activities are carried out in this field, is rapidly changing the reality of accounting. Over the years, accounting has significantly transformed from paper-and-pencil work to the use of computers. More importantly, accounting has evolved with programs that reduce time spent on repetitive tasks and decrease the occurrence of errors. The interest in AI solutions in this field is not new, but in recent years, researchers’ attention has increasingly focused on it. Despite technological advancements, there appears to be insufficient data to support companies’ willingness to integrate AI solutions into their accounting activities. An important aspect of this reality is the ability of professionals to adapt more quickly to the current situation and acquire the necessary skills to work with AI solutions, overcoming the fear of job loss. This article focuses on understanding the impact of AI solutions on accounting by conducting a qualitative study based on a review of the relevant literature from previous years. It highlights the potential changes that AI could bring to accounting professions and the necessary actions to prepare for the emergence of new jobs where AI solutions will play a larger role.